2021
DOI: 10.1016/j.ijcard.2020.11.055
|View full text |Cite
|
Sign up to set email alerts
|

Early and late post-operative arrhythmias after surgical myectomy: 45 years of follow-up

Abstract: Aims: The aims of this study are to investigate the incidence and determinants of post-operative atrial arrhythmias, conduction disorders and mortality in hypertrophic obstructive cardiomyopathy (HOCM) patients undergoing transaortic myectomy. Methods and results: This retrospective single-center study was conducted in 249 patients (median age 54 years , 42% female) undergoing transaortic myectomy. Post-operative atrial fibrillation (AF) was reported in 84 patients (33.7%), including 56 patients (22.5%) with d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 32 publications
(50 reference statements)
1
3
0
Order By: Relevance
“…Patients’ demographic data were comparable with statistics reported by Romanian Registry of Hypertrophic Cardiomyopathy [ 9 ] or other cohorts of Romanian patients with HCM [ 10 ], with a mean age falling in the sixth decade of life, and with male predominance. Baseline clinical characteristics and echocardiography findings were similar with those from other European centres [ 11 , 12 ]. Preoperatively, the majority of our subjects (59%) were either in NYHA class III or IV, with a mean IVS thickness of 24 ± 6 mm and a mean LVOT gradient of 93 ± 33 mmHg.…”
Section: Discussionsupporting
confidence: 78%
“…Patients’ demographic data were comparable with statistics reported by Romanian Registry of Hypertrophic Cardiomyopathy [ 9 ] or other cohorts of Romanian patients with HCM [ 10 ], with a mean age falling in the sixth decade of life, and with male predominance. Baseline clinical characteristics and echocardiography findings were similar with those from other European centres [ 11 , 12 ]. Preoperatively, the majority of our subjects (59%) were either in NYHA class III or IV, with a mean IVS thickness of 24 ± 6 mm and a mean LVOT gradient of 93 ± 33 mmHg.…”
Section: Discussionsupporting
confidence: 78%
“…Advancing age is the most widely proven major predictor in the occurrence of POAF [27][28][29][30][31]. In patients aged 72 years or older, the risk of POAF is approximately five times greater than in patients who are aged 55 or younger [2].…”
Section: Agementioning
confidence: 99%
“…To date, the only studies have drawn inconsistent conclusions. 11 , 12 , 13 Although further studies are needed on the impact of POAF on long‐term clinical course in OHCM, we speculate that the impact of POAF on the prognosis of patients with OHCM is less severe than that of patients with other cardiovascular conditions.…”
Section: Discussionmentioning
confidence: 91%
“…The few previous studies have determined that the impact of POAF on the prognosis of the disease is different between patients with OHCM and other cardiac surgical populations, which suggests that POAF in OHCM is unique. 11 , 12 , 13 As a common complication after cardiac surgery, previous studies have shown that the occurrence of POAF in Chinese population is significantly lower than that in other ethnic groups. 14 , 15 This suggests that the clinical phenotype of cardiovascular disease in Chinese population may be different from that in other populations.…”
Section: Discussionmentioning
confidence: 98%